PENGARUH MEDIA PEMBELAJARAN ETNOMATEMATIKA BERBASIS WEBSITE TERHADAP KEMAMPUAN NUMERASI SISWA KELAS IV SDN 248 PALEMBANG - Siregar, Meliana; Aryaningrum, Kiki; Sunedi, Sunedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of website-based learning media on the numeracy skills of fourth-grade students of SDN 248 Palembang. This study uses a quantitative method with a true experimental design. This study uses two classes, namely the experimental class which is given treatment using website-based ethnomathematics learning media and the control class using conventional methods. All fourth-grade students are the research population, and sampling is done by simple random sampling. The research sample consisted of 63 students, divided into classes IV.A (32 students) and IV.C (31 students). Data collection was carried out by giving an initial test (pretest) and a final test (posttest) to both classes. Before testing the hypothesis, a normality and homogeneity test was carried out. Furthermore, the hypothesis test used the T-Test (Independent Sample T-Test). The results of the study showed that the t-count value (3.057) > t-table (1.670) was 3.057 > 1.670 with a significance level of 5%. Based on these results, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, which means that there is a significant difference between the numeracy abilities of students in the experimental class and the control class after being given treatment. It is proven that the use of website-based ethnomathematics learning media has an effect on students' numeracy abilities. The average posttest score of students in the experimental class (83.31) is higher than that of the control class (75.24). Thus, it can be concluded that website-based ethnomathematics learning media is effective in improving students' numeracy abilities.